Structural constraints determine the glycosylation of HIV-1 envelope trimers - Pritchard, Laura K. (Cell Rep, 2015)
A highly glycosylated, trimeric envelope glycoprotein (Env) mediates HIV-1 cell entry. The high density and heterogeneity of the glycans shield Env from recognition by the immune system but, paradoxically, many potent broadly neutralizing antibodies (bNAbs) recognize epitopes involving this glycan shield. To better understand Env glycosylation and its role in bNAb recognition, we characterized a soluble, cleaved recombinant trimer (BG505 SOSIP.664) that is a close structural and antigenic mimic of native Env. Large, unprocessed oligomannose-type structures (Man(8-9)GlcNAc(2)) are notably prevalent on the gp120 components of the trimer, irrespective of the mammalian cell expression system or the bNAb used for affinity-purification. In contrast, gp41 subunits carry more highly processed glycans. The glycans on uncleaved, non-native oligomeric gp140 proteins are also highly processed. A homogeneous, oligomannose-dominated glycan profile is therefore a hallmark of a native Env conformation and a potential Achilles’ heel that can be exploited for bNAb recognition and vaccine design.